Smart Car with Security Camera for Road Accidence Monitoring - Poonsak Sirichai; Somkuan Kaviya; Yusaku Fujii; Preecha P. Yupapin (My University, 2011)
Abstract This research proposes the concept of security and prevention of road accidence using close circuit television (CCTV) monitoring system in conjunction with the vehicular ad hoc networks (VANET), which is integrated by a 3G or 4G cellular wireless networks. By using the CCTV cameras installed in taxi (car), the image is converted to wireless signal and transmitted via the radio system, in which the communication between cars and taxi call centre can be provided. Moreover, the security of image can be protected by using the signal encryption technique, in which the secret key is available only by authorized person, where finally the required image can be viewed when the crime is occurred. This is the security concept with the privacy violation and protection.
Keywords: Vehicular Ad Hoc Networks (VANETs)